2008
DOI: 10.1136/thx.2007.091686
|View full text |Cite
|
Sign up to set email alerts
|

Combined endoscopic approach in the treatment of benign broncho-oesophageal fistula

Abstract: The treatment of benign broncho-oesophageal fistula is usually surgical but sometimes other methods of treatment are preferred. The case history is described of an adult in poor general condition in which an endoscopic approach combined with the use of fibrin glue on the bronchial side and metallic clips on the oesophageal side was used to close the fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…A search of the English and Japanese literature revealed only eight cases of EBF or esophagotracheal fistula attributable to an esophageal foreign body. Table 1 summarizes the details of those cases [1][2][3][4][5][6] as well as those of our present case. Although Mangi et al 1) reported that benign EBF was mainly right-sided in their case series, EBF caused by a foreign body in the esophagus was observed more frequently on the left side in other reports.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A search of the English and Japanese literature revealed only eight cases of EBF or esophagotracheal fistula attributable to an esophageal foreign body. Table 1 summarizes the details of those cases [1][2][3][4][5][6] as well as those of our present case. Although Mangi et al 1) reported that benign EBF was mainly right-sided in their case series, EBF caused by a foreign body in the esophagus was observed more frequently on the left side in other reports.…”
Section: Discussionmentioning
confidence: 95%
“…Seven of the eight cases reported in the literature were treated surgically and one was treated endoscopically. [1][2][3][4][5][6] All thoracic surgical interventions were performed through a right thoracotomy, which may simply reflect the fact that many thoracic surgeons prefer to perform esophageal surgery via right thoracotomy. We agree that right thoracotomy has advantages when there is a need to manipulate the esophagus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this procedure seems more suitable for congenital fistulas of moderate size [15] . Endoscopic insertion of self-expandable metal stents is mainly indicated to palliate symptoms in neoplastic patients with a poor prognosis [16] , [17] . Another endoscopic option is the combined injection of fibrin glue by means of bronchoscopy, and the insertion of a metal clip by esophagoscopy [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Some centers have utilized stenting, adhesives, or occlusives when surgical treatment is contraindicated or when a patient declines surgical management. Adhesives and occlusives may consist of fibrin glue, cyanoacrylate glue, bovine collagen, gelfoam, metallic coils, or metallic clips (57), and can produce good outcomes in patients with small fistulae without local infection but is less successful in patients with large diameter fistulae. In the present case, metallic coils and cyanoacrylate glue were unsuccessful due to the absence of a defined tract between the carina and the dilated diverticulum-like esophageal wall.…”
Section: Discussionmentioning
confidence: 99%